Presentation skills for students - Van Emden, Joan (Palgrave Macmillan, 2010)
Previous ed.: 2004; Includes bibliographical references and index; Machine generated contents note: Preface -- Personal Development: Speaking to an Audience -- Delivery and Non-verbal Communication and Nerves -- Choosing and Using Visual Aids -- Speaking as Part of Your Course -- Speaking as Part of a Group -- Speaking as a Student Representative -- Speaking at Elections and Meetings -- Job Searches and Job Interviews